Ginsenoside Rg3 Improved Age-Related Macular Degeneration Through Inhibiting ROS-Mediated Mitochondrion-Dependent Apoptosis In Vivo and In Vitro - Hu, Rui-Yi; Qi, Si-Min; Wang, Ya-Jun; Li, Wen-Lin; Zou, Wan-Chen; Wang, Zi; Ren, Shen; Li, Wei (International journal of molecular sciences, 2024)
Age-related macular degeneration (AMD) is marked by a progressive loss of central vision and is the third leading cause of irreversible blindness worldwide. The exact mechanisms driving the progression of this macular degenerative condition remain elusive, and as of now, there are no available preventative measures for dry AMD. According to ancient records, ginseng affects the eyes by brightening them and enhancing wisdom. Modern pharmacological research shows that the active ingredients in ginseng, ginsenosides, may be used to prevent or improve eye diseases that threaten vision. Some articles have reported that ginsenoside Rg3 can treat diabetic retinopathy in mice, but no reports exist on its effects and mechanisms in AMD. Therefore, the role and mechanism of ginsenoside Rg3 in AMD warrant further study. This study aims to investigate the effects of Rg3 on AMD and its underlying molecular mechanisms. We established a mouse model of AMD to examine the impact of ginsenoside Rg3 on NaIO3-induced apoptosis in the retina and to explore the related intrinsic mechanisms. The in vivo results indicated that ginsenoside Rg3 prevents NaIO3-induced apoptosis in retinal pigment epithelial cells by inhibiting reactive oxygen species production and preventing the reduction in mitochondrial membrane potential. Additionally, we assessed the levels of protein expression within the apoptosis pathway. Ginsenoside Rg3 decreased the expression of Bax, cleaved caspase-3, and cleaved caspase-9 proteins. Additionally, it increased the expression of Bcl-2 by decreasing P-JNK levels. Moreover, our in vivo results showed that ginsenoside Rg3 enhanced retinal structure, increased the relative thickness of the retina, and decreased the extent of disorganization in both the inner and outer nuclear layers. Ginsenoside Rg3 may safeguard the retina against NaIO3-induced cell apoptosis by attenuating reactive-oxygen-species-mediated mitochondrial dysfunction, in which the JNK signaling pathway is also involved. These findings suggest that ginsenoside Rg3 has the potential to prevent or attenuate the progression of AMD and other retinal pathologies associated with NaIO3-mediated apoptosis.